Covert Aggression and Gifted Adolescent Girls - Phelps, Connie; Beason-Manes, Ashley; Lockman, Amy (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2020)
While considerable research exists on bullying in P-12 schools, few empirical studies address bullying and gifted students. Moreover, the field of Gifted, Talented, and Creative Education lacks single construct studies on covert aggression and gifted students. Also known as relational aggression, covert aggression purposefully manipulates relationships and damages reputations through less obvious or hidden forms of bullying. This exploratory study in a Midwest state analyzed quantitative and qualitative data gathered from 27 gifted adolescent girls on covert aggression instances with intellectual and non-exceptional female peers during 6th, 7th, and 8th grades. Participants tallied incidents of covert aggression, provided short written comments, and participated in structured group interviews. Of 1037 incidents, covert aggression occurred most prevalently during 7th grade. Participants indicated fewer incidents with their intellectual peers than with non-exceptional peers. Academic topics of intelligence, grades, and name calling formed a cluster of incidents most frequently experienced with intellectual and non-exceptional peers. Participants attributed covert aggression to their differentness from non-exceptional peers. Covert aggression topics of intelligence and grades with intellectual peers seemed linked with negative aspects of competition. Participants found support from intellectual peers at school who provided empathy for their advanced abilities. Prevalence and subjective experience results from both groups indicated gifted adolescent girls encounters with covert aggression impeded development of their giftedness and full inclusion in secondary school environments. Peer support groups that recognize covert aggression behaviors and practice intervention strategies might ameliorate its harmful effects and improve the social-emotional wellness of gifted adolescent girls.